2023
DOI: 10.3390/biology12020157
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Thrive: Impaired BDNF Transport along the Cortical–Striatal Axis in Mouse Q140 Neurons of Huntington’s Disease

Abstract: Boosting trophic support to striatal neurons by increasing levels of brain-derived neurotrophic factor (BDNF) has been considered as a target for therapeutic intervention for several neurodegenerative diseases, including Huntington’s disease (HD). To aid in the implementation of such a strategy, a thorough understanding of BDNF cortical–striatal transport is critical to help guide its strategic delivery. In this manuscript, we investigate the dynamic behavior of BDNF transport along the cortical–striatal axis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Indeed, mouse primary neuron models that employ the lentiviral transduction of mHTT exon 1 display the downregulation of Bdnf gene expression well before decrements in measures of viability [ 104 , 105 ]. Untransfected primary neurons harvested from embryonic-age HD mouse models also displayed aberrations in BDNF expression, transport, or release in culture [ 106 , 107 , 108 ]. More innovative approaches, including induced pluripotent stem cells (iPSCs) and the direct reprogramming of fibroblasts obtained from HD patients, are increasingly used to model HD [ 109 ].…”
Section: The Role Of Bdnf In Hdmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, mouse primary neuron models that employ the lentiviral transduction of mHTT exon 1 display the downregulation of Bdnf gene expression well before decrements in measures of viability [ 104 , 105 ]. Untransfected primary neurons harvested from embryonic-age HD mouse models also displayed aberrations in BDNF expression, transport, or release in culture [ 106 , 107 , 108 ]. More innovative approaches, including induced pluripotent stem cells (iPSCs) and the direct reprogramming of fibroblasts obtained from HD patients, are increasingly used to model HD [ 109 ].…”
Section: The Role Of Bdnf In Hdmentioning
confidence: 99%
“…Although no significant evidence exists to support the specific disruption of trafficking of the Bdnf transcript in HD, we note that others have shown that BDNF and its transcripts are co-segregated in neurons [ 161 ]. Therefore, reports of altered BDNF protein distribution and transportation across degrading trafficking networks within HD neurons may be equally applicable to its transcript [ 79 , 108 , 118 ].…”
Section: Mechanisms Of Bdnf Gene Regulation In Hdmentioning
confidence: 99%
“…219 BDNF activities are bargained in HD, probably since the mHTT impairs its cortico-striatal transport, thus causing striatal neurodegeneration. 220,221 Wild-type HTT adjusts BDNF transport and indirectly improves the BDNF genetic expression, while BDNF overexpression brings about phenotypic recovery in a rodent model of HD. 222 Recently, iPSCs-derived NSCs therapy decreased behavioral dysfunctions and ameliorated neuropathological alterations in the YAC128 mouse model of HD in part by elevating BDNF and TrkB levels in striata of treated mice.…”
Section: Hdmentioning
confidence: 99%
“…Further, given that BDNF is a critical neurotrophic factor for the cortico‐striatal synaptic activity and the survival of GABAergic neurons, therapeutic effects of BDNF‐overexpressing human NSCs (BDNF‐HB1.F3) has been assessed in HD rat model 219 . BDNF activities are bargained in HD, probably since the mHTT impairs its cortico‐striatal transport, thus causing striatal neurodegeneration 220,221 . Wild‐type HTT adjusts BDNF transport and indirectly improves the BDNF genetic expression, while BDNF overexpression brings about phenotypic recovery in a rodent model of HD 222 .…”
Section: Engineered Nscs In Chronic Neurological Diseasesmentioning
confidence: 99%